Rasch Analysis of the Disability Acceptance Scale for Individuals With Cerebral Palsy - Park, Eun-Young (Frontiers in Neurology, 2019)
Background: The acceptance of disability has been considered an important factor in rehabilitation procedures. The Disability Acceptance Scale (DAS) was used in a panel survey and it is likely that this scale will be increasingly used. This study aimed to determine the psychometric characteristics of the DAS by applying a Rasch model, an application of item response theory. Methods: Data were collected by using the DAS for 84 individuals with cerebral palsy. The response data were analyzed for item fitness and item difficulty, rating scale fit, and reliability. Results: Three of the nine DAS items had low fitness. Analysis of item difficulty showed that the item difficulty needs to be modified, suggesting the need to add some items with higher difficulty and some with lower difficulty. The 5-point Likert scale used in the evaluation questionnaires was not appropriate. An analysis of the six remaining items showed high levels of subject separation reliability and separation reliability of the items. Conclusions: This study is significant because it identified the psychometric characteristics of the DAS through item response theory-based Rasch analysis and suggested the need to modify the item fitness and difficulty level. A modified six-item version of the DAS with a 4-point Likert scale was proposed as being more suitable.